Succession in Large Nineteenth-Century Chilean Family Businesses - Nazer-Ahumada, J; Llorca-Jana, M (Routledge, 2022)
This article analyses the process of succession in three large Chilean family businesses between c.1860s-1940s, whose combined wealth was 10% of Chilean GDP. Although there is no general theory of succession planning in family firms, the most common reasons for why succession fails or succeeds have been identified in the specialised literature. We have contrasted the evidence we found in our three case studies against the theories available. The theories underpinning effective successions are supported by the case studies under analysis: timely selection and training of a competent successor; a reduced number of heirs; strategically arranged marriages; and family harmony. Some of the theories behind succession failure are also borne out by the existing evidence: family rivalries; adverse external economic shocks; conflicts between the family and the government; lack of commitment on the part of the heirs to the continuity of the business; unskilled successors taking over; early deaths from illness. Two further underlying elements can be identified from the Chilean case studies: fragmentation of the capital of the group; and the fashion for family members to spend time in Europe as rentiers. © 2020 Informa UK Limited, trading as Taylor & Francis Group.